THE INFLUENCE OF THE DEVELOPMENT OF THE DIGITAL CREATIVE ECONOMY ON THE CONSUMPTIVE BEHAVIOR OF YOUNG WOMEN - Didon Pramandhita, Didon Pramandhita; Asep Saifudin, Asep Saifudin; Henny Risnawaty, Henny Risnawaty; Moedigdo Sigit Prakoso , Moedigdo Sigit Prakoso (Cakrawala Akuntansi & Manajemen, 2024)
This study aims to analyze the digital creative economy's influence on young women's consumptive behavior. With the development of technology and the internet, young women are increasingly exposed to various digital content influencing their lifestyles and consumption patterns. Data were obtained through a survey involving young women aged 15-18 years in the Jatiranggon sub-district, Jatisampurna district, Bekasi city. The results of the study showed a significant correlation between exposure to digital creative economy content and increased consumptive behavior in young women.